Pengaruh Human Capital, Emotional Inteligence Dan Self Efficacy Terhadap Kinerja Pegawai Dimoderasi Oleh Organizational Citizenship Behavior (OCB) - Rizal, Fahmi (Jurnal Ekonomi Manajemen Sistem Informasi, 2024)
This research aims to analyze the influence of Human Capital, Emotional Intelligence, and Self-Efficacy on employee performance, with a specific focus on the moderation effect of Organizational Citizenship Behavior (OCB). Data were collected from respondents in various organizations, and regression analysis was employed to examine the relationships between variables. The findings indicate that Human Capital significantly contributes to employee performance, and both Emotional Intelligence and Self-Efficacy also exhibit a positive and significant impact. Furthermore, OCB moderates the relationship between the independent variables and employee performance, suggesting that employees` voluntary behaviors can enhance or diminish the influence of these factors. The results of this study provide insights into how human resource management and organizational culture can enhance employee performance in complex work environments.